Combating Risks in Dentistry During Covid-19 Pandemic (Indian Journal of Forensic Medicine & Toxicology, 2020)
The year 2019- 2020 has given rise to a menace in the form of Corona Virus Disease, which within notime has turned into a pandemic, affecting every corner of the world. It has disarranged the day-to-daylifestyle of the society, economy, employment, trade, hunger, etc. Dentistry is also one of these, affectedby the pandemic, and has caused heavy financial loss for the dental personnel, along with delay/halt in thedental treatment to a massive population in need. When eradicating the disease has become a question, it isbetter to live with the disease and restrain the risks of transmission in the dental operatory by following fewcrucial and mandatory steps like proper hand hygiene, maintaining social distancing, creating awareness,fumigating the operating rooms and surfaces etc. This review article thus elaborates the expedients a dentalsurgeon should follow to combat the risks of transmission of this fierce disease during dental interventions.
Keywords: COVID-19, Dentistry, Infection, Transmission, Risk.